Model of unidirectional block formation leading to reentrant ventricular tachycardia in the infarct border zone of postinfarction canine hearts. (1st July 2015) - Ciaccio, Edward J.; Coromilas, James; Ashikaga, Hiroshi; Cervantes, Daniel O.; Wit, Andrew L.; Peters, Nicholas S.; McVeigh, Elliot R.; Garan, Hasan
Abstract: Background: When the infarct border zone is stimulated prematurely, a unidirectional block line (UBL) can form and lead to double-loop (figure-of-eight) reentrant ventricular tachycardia (VT) with a central isthmus. The isthmus is composed of an entrance, center, and exit. It was hypothesized that for certain stimulus site locations and coupling intervals, the UBL would coincide with the isthmus entrance boundary, where infarct border zone thickness changes from thin-to-thick in the travel direction of the premature stimulus wavefront. Method: A quantitative model was developed to describe how thin-to-thick changes in the border zone result in critically convex wavefront curvature leading to conduction block, which is dependent upon coupling interval. The model was tested in 12 retrospectively analyzed postinfarction canine experiments. Electrical activation was mapped for premature stimulation and for the first reentrant VT cycle. The relationship of functional conduction block forming during premature stimulation to functional block during reentrant VT was quantified. Results: For an appropriately placed stimulus, in accord with model predictions: (1) The UBL and reentrant VT isthmus lateral boundaries overlapped (error: 4.8±5.7 mm). (2) The UBL leading edge coincided with the distal isthmus where the center-entrance boundary would be expected to occur. (3) The mean coupling interval was 164.6±11.0 ms during premature stimulation and 190.7±20.4 ms during the first reentrant VT cycle, in accord with model calculations, which resulted in critically convex wavefront curvature with functional conduction block, respectively, at the location of the isthmus entrance boundary and at the lateral isthmus edges. Discussion: Reentrant VT onset following premature stimulation can be explained by the presence of critically convex wavefront curvature and unidirectional block at the isthmus entrance boundary when the premature stimulation interval is sufficiently short. The double-loop reentrant circuit pattern is a consequence of wavefront bifurcation around this UBL followed by coalescence, and then impulse propagation through the isthmus. The wavefront is blocked from propagating laterally away from the isthmus by sharp increases in border zone thickness, which results in critically convex wavefront curvature at VT cycle lengths. Highlights: Ventricular tachycardia is common after myocardial infarction and it is a serious health problem worldwide. The source of reentrant ventricular tachycardia is often located in the infarct border zone, the layer of thin surviving myocardium adjacent to the infarct. Although there is electrical activity occurring in the infarct border zone, the conduction velocity of the leading edge of the propagating wavefront is not constant. Where the infarct border zone dimension changes from thin-to-thick in the travel direction, very slow conduction or even functional block occur at locations where the wavefront becomes critically convex. In this study, the activation rate and IBZ geometric structure necessary for functional block to form during premature stimulation and during reentrant ventricular tachycardia, are determined.